(untitled) (Journal of the College of Basic Education, 2026)
The study addresses the concept of residential neighborhoods, or housing communities, designed in an organized manner to provide an integrated environment that meets the needs of residents. These neighborhoods include essential services and facilities that contribute to strengthening social ties and reducing societal fragmentation. The study focuses on the Al-Qadisiyah residential neighborhood located in the center of the Madain district, analyzing its location and significance as well as the spatial distribution of urban land uses. The aim of the study is to understand the nature of the services provided to the residents, identify strengths and weaknesses, and evaluate areas for improvement. The findings revealed a shortage in educational and recreational services, emphasizing the need to enhance these aspects due to their importance for the community of the neighborhood.